1994
DOI: 10.3109/15513819409037698
|View full text |Cite
|
Sign up to set email alerts
|

Role of Asphyxia and Feeding in a Neonatal Rat Model of Necrotizing Enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a common gastrointestinal disorder affecting premature infants. To investigate critically the importance of the purported risk factors of NEC (formula feeding, asphyxia, bacteria, and prematurity), we developed a neonatal rat model that closely mimics the human disease. Full-term and premature newborn rats were stressed with formula feeding, asphyxia, and/or exogenous bacterial colonization and subsequently evaluated grossly and histologically for the development of intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
1
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 29 publications
7
141
1
6
Order By: Relevance
“…This increase corresponded to a total of about 1,000 neutrophils distributed over the entire small intestine. In combination with the low transcriptional activity of proinflammatory cytokines measured in this study, this slight increase of neutrophils is well in line with the minimal inflammation seen in experimental murine NEC by other groups (13,29).…”
Section: Articlessupporting
confidence: 67%
See 2 more Smart Citations
“…This increase corresponded to a total of about 1,000 neutrophils distributed over the entire small intestine. In combination with the low transcriptional activity of proinflammatory cytokines measured in this study, this slight increase of neutrophils is well in line with the minimal inflammation seen in experimental murine NEC by other groups (13,29).…”
Section: Articlessupporting
confidence: 67%
“…Grade 0: intact epithelium with villus structure; 1: superficial epithelial cell sloughing; 2: mid-villous necrosis; 3: complete villous necrosis; and 4: transmural necrosis. Samples with histological scores of 3 or higher were considered positive for NEC (modified protocol of Caplan et al (29)). The modification was made to ensure positive selection for NEC by excluding unlikely graded artificial lesions, as observed in some breastfed animals, caused by luminal air bubbles during the fixation process which might mimic "grade 2 " lesions (Supplementary Figure S3 online).…”
Section: Histologic Injury Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Additional experiments have evaluated the importance of PAF in neonatal rats using the typical risk factors of NEC, including asphyxia and formula feeding [16]. In this model, we have shown that PAF receptor blockade reduces the incidence of NEC, and that the PAF-degrading enzyme PAF-AH given with enteral feeding interferes with the initiation of NEC [17,18].…”
Section: The Role Of Platelet Activating Factor Homeostasismentioning
confidence: 99%
“…A combinação de isquemia gastrointestinal, fruto de uma redistribuição do fluxo sangüíneo esplâncnico para órgãos vitais como coração e cérebro, alimentação enteral, possivelmente predispondo à lesão da camada mucosa e mais a translocação de bactérias patogênicas, tudo isto associado a uma imaturidade dos mecanismos imunitários intestinais, estariam envolvidos em seu desenvolvimento 1,2 . Muitos modelos animais foram usados para avaliar os efeitos da hipóxia na etiopatogenia da ECN e demonstraram que o decréscimo da perfusão intestinal e que a lesão tecidual seriam causadas por um mecanismo de isquemia e reperfusão [3][4][5][6][7][8][9][10][11][12] . O objetivo de nosso estudo é avaliar um modelo experimental de ECN em ratos proposto por em 1995 por Okur e col. 9 .…”
Section: Introductionunclassified